Possible discrepancies between cosmological and electroweak observables in Higgs Inflation - Jamerson G. Rodrigues (SpringerOpen, 2021)
Abstract In this work, we revisit the non-minimally coupled Higgs Inflation scenario and investigate its observational viability in light of the current Cosmic Microwave Background, Baryon Acoustic Oscillation and type Ia Supernovae data. We explore the effects of the Coleman-Weinberg approximation to the Higgs potential in the primordial universe, connecting the predictions for the Lagrangian parameters at inflationary scales to the electroweak observables through Renormalization Group methods at two-loop order. Initially, we find that electroweak scale measurements may be dissonant to the limits obtained from the cosmological data sets used in the analysis. Specifically, an ≈ 8σ-discrepancy between the inflationary parameters and the value of the Monte Carlo reconstructed top quark mass is found. However, considering the most recent results obtained by the CMS Collaboration from differential cross-section measurements of the top quark production a good agreement is obtained.